ALGORITHM FOR SEARCHING SMALL CYCLES IN GRAPH - YUDHA SULISTIANDA (NIM : 10108003); Pembimbing : Prof. Dr. Edy Tri Baskoro, EKA
The study of cycles in a graph is one of interesting topics in graph theory. Such studies include the study of determining whether a graph having a Hamiltonian cycle or not; and the study of finding a smallest cycle in a given graph. Detecting cycles in graphs has also important applications in some other fields, for instances in chemistry, biology, computer science and others. The aim of this project is to propose an algorithm for detecting certain small cycles and/or a smallest cycle in a given graph. The algorithm has been implemented for detecting cycles on several well-known classes of graphs.